2016
DOI: 10.1155/2016/2947510
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of CdS Sensitized TiO2Photocatalysts: Methylene Blue Adsorption and Enhanced Photocatalytic Activities

Abstract: A series of CdS/TiO2nanocomposites with different Cd to Ti molar ratio were synthesized from P25-TiO2nanopowder using microwave-assisted hydrothermal method. The as-produced powders were characterized by XRD, electron microscopy, EDX, and UV-Vis diffuse reflectance spectroscopy. The adsorption capacity and photocatalytic activity of the samples were investigated using methylene blue as a model pollutant. Sorption tests revealed that the adsorption of MB onto the samples obeys the Freundlich-Langmuir isotherm m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 55 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…After 150 min of illumination, the average decolorization was improved to 89%, 82%, 85%, 92%, and 89% approximately for Clayx, ZnTiO 3 /TiO 2 -Clayx, TiO 2 -Clayx, ZnTiO 3 /TiO 2, and TiO 2 , respectively, which confirmed that adsorption combined with photocatalysis is an efficient process for dye degradation. These results agree with those obtained by other authors for the degradation of MB by adsorption and photocatalysis [66][67][68][69][70][71].…”
Section: Adsorption and Photocatalytic Degradationsupporting
confidence: 93%
“…After 150 min of illumination, the average decolorization was improved to 89%, 82%, 85%, 92%, and 89% approximately for Clayx, ZnTiO 3 /TiO 2 -Clayx, TiO 2 -Clayx, ZnTiO 3 /TiO 2, and TiO 2 , respectively, which confirmed that adsorption combined with photocatalysis is an efficient process for dye degradation. These results agree with those obtained by other authors for the degradation of MB by adsorption and photocatalysis [66][67][68][69][70][71].…”
Section: Adsorption and Photocatalytic Degradationsupporting
confidence: 93%
“…The KM plot is similar to the Tauc plot which is obtained from the absorption spectra. The KM function F(R) is obtained using equation (5) [33].…”
Section: Methodsmentioning
confidence: 99%
“…Titania is extensively employed in energy-associated industries, specifically, in water splitting under visible-light irradiation [6]. However, different compounds have been used for the doping of TiO 2 with CdS [7]. SnO 2 -doped TiO 2 [8][9][10], WO 3 -doped TiO 2 [11], ZrTiO 4 [12][13][14], and are employed in the heterogeneous photocatalysis.…”
Section: Introductionmentioning
confidence: 99%